An Overview of Biological Treatment Concepts for Nickel and Cobalt Recovery, and SO, Removal - J. L. Huisman; G. Schouten (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
After pyrometallurgy and hydrometallurgy, bio(hydro)metallurgy is the latest development in the ongoing search for efficient and economic metal winning processes. In addition to bioleaching, other biotechnology-based applications are getting more and more accepted. In this paper a number of proven and commercial processes will be presented that can be applied for nickel and cobalt recovery and refining. These processes are based on the ability of biomass to convert the redox state of sulphur compounds under ambient conditions. They can be applied to recover sulphate from effluents or SOx from off gases and convert it to H2S or dissolved sulphide that can be reused in production or effluent treatment. Not only does this minimize the costs on resources but it also reduces waste production and improves the quality of discharges even to the point where reuse becomes feasible.